966 Implementation of Regional Scalp Blockade for Painless Removal of ICP Bolts: A Quality Improvement Project. (4th May 2021) - de Gouveia, M; Craven, C L; Goel, A; Asif, H; Das, P; Thorne, L; Watkins, L; Toms, A
Abstract: Introduction: Intracranial pressure (ICP) monitoring through insertion of a bolt is a common neurosurgical procedure for diagnosing cerebrospinal fluid disorders. The first step of our quality improvement project identified ICP bolt removal the most painful part of the procedure. We implemented and tested the efficacy of a scalp nerve block for bolt removal. Method: Two groups were identified: (A) receiving oral analgesia only and (B) receiving ipsilateral supraorbital and supratrochlear nerve blocks. We then retrospectively compared satisfaction ratings of insertion versus removal process for the two bolt types using a telephonic questionnaire Results: Eighty-five patients had ICP bolts (32M:53F, mean age 42.7±16.0 SD). Fifty-four were removed with oral analgesia (A) and 31 with oral and regional anaesthesia (B). Removal experience was reported as worse for group A than for group B (p < 0.01). Most patients (66%) reported would have preferred local anesthetic during removal. No complications occurred from the block. Conclusions: Regional nerve blocks are a safe and effective adjuvant for the painless removal of frontal ICP monitoring bolts. The final stage of the project was to implement nerve blocks as standard practice for bolt removal, to improve patient experience.